Faculty perspectives on challenges faced by students with disabilities in bachelor’s programs - Altaweel, Nora; Alnajashi, Sumyah; Shabi, Fatimah; Althaqafi, Ahmed (Frontiers in Education, 2026)
This study explores faculty members’ perceptions of challenges faced by students with disabilities enrolled in bachelor’s degree programs within a specific geographical context in Saudi Arabia. It further investigates whether statistically significant differences in the severity of these perceived challenges, as measured by the study questionnaire, based on teaching experience with students with disabilities as well as college category variables. A total of 256 faculty members completed an online questionnaire, which was developed around five axes. Descriptive statistics and inferential analyses were used to examine trends and group differences, and the results identified significant challenges associated with implementing policies for enrollment, services provided to students with disabilities, faculty awareness of support, and the accommodations on campus. Conversely, they did not perceive bachelor’s programs as incompatible with students with disabilities. The results indicated no significant differences between those with and without prior teaching experience, yet a significant effect of discipline was found on the extent to which faculty members agreed on these challenges, favoring those in the humanities disciplines. Implications for the university enrollment of students with disabilities are also discussed.